BBPR. Sede Hispano-Olivetti a Barcellona - Lisini, Caterina (Firenze Architettura, 2021)
The Hispano Olivetti headquarters in Barcelona by the BBPR Group can be considered as an exemplary work in the process of the construction of an aesthetic expression in architecture. A skillful and complex creation, which reveals the difficulties in achieving harmony in an architectural work, in a precarious balance between respect for the culture of places, the formal tradition of the context, and invention in the wake of modern experimentation.